2014
DOI: 10.1016/j.braindev.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase 2 gene polymorphism is a genetic risk factor for sudden unexpected death in infancy

Abstract: Rationale: Carnitine palmitoyltransferase (CPT) II is one of a pivotal enzyme in mitochondrial fatty acid oxidation, which is essential for energy production during simultaneous glucose sparing and a requirement for major energy supply, such as prolonged fasting or exercise. When infants require more energy than provided by the glycolytic system, they rely on the mitochondrial fatty acid oxidation pathway.Mutations of the CPT2 gene have been reported to cause sudden unexpected death in infancy (SUDI). A thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…CPT II is a pivotal enzyme in mitochondrial fatty acid oxidation, which is essential for energy production during simultaneous glucose sparing and a requirement for major energy supply, such as during prolonged fasting or exercise [31]. Cases with the thermolabile genetic phenotype of CPT II have been described mainly in Japan and China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPT II is a pivotal enzyme in mitochondrial fatty acid oxidation, which is essential for energy production during simultaneous glucose sparing and a requirement for major energy supply, such as during prolonged fasting or exercise [31]. Cases with the thermolabile genetic phenotype of CPT II have been described mainly in Japan and China.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with the thermolabile genetic phenotype of CPT II have been described mainly in Japan and China. Recent studies have suggested the association of this phenotype with influenza-associated encephalopathy, encephalopathy during a high-grade fever caused by human herpesvirus-6, enterovirus 71, Echo virus, Coxsackievirus, rotavirus, respiratory syncytial virus, adenovirus infection, or sudden unexpected death in infancy [3140]. Generally, CPT II deficiency has three clinical presentations: a lethal neonatal form, a severe infantile hepatocardiomuscular form, and a myopathic form (which is usually mild and can manifest from infancy to adulthood) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin transporter polymorphism was first reported by Narita et al 3 We also reported that the carnitine palmitoyltransferase2 variant is a risk factor. 4 Other than these, there are variants of arrhythmia channel genes, which are detected in healthy controls and which affect the cardiac ion channel currents. There are no studies, however, on the genetic frequencies of these arrhythmia channel gene variants, and it is controversial as to whether these variants are associated with SUD in infancy.…”
mentioning
confidence: 99%
“…Since these two substitutions are common genetic polymorphisms [18], [19], [20], [21], [22], they were excluded from the targeted NGS analysis.…”
Section: Resultsmentioning
confidence: 99%